If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(x + -1) = 4x + -1 Reorder the terms: 5(-1 + x) = 4x + -1 (-1 * 5 + x * 5) = 4x + -1 (-5 + 5x) = 4x + -1 Reorder the terms: -5 + 5x = -1 + 4x Solving -5 + 5x = -1 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. -5 + 5x + -4x = -1 + 4x + -4x Combine like terms: 5x + -4x = 1x -5 + 1x = -1 + 4x + -4x Combine like terms: 4x + -4x = 0 -5 + 1x = -1 + 0 -5 + 1x = -1 Add '5' to each side of the equation. -5 + 5 + 1x = -1 + 5 Combine like terms: -5 + 5 = 0 0 + 1x = -1 + 5 1x = -1 + 5 Combine like terms: -1 + 5 = 4 1x = 4 Divide each side by '1'. x = 4 Simplifying x = 4
| 11x-4=26x+6 | | x+25=100 | | 4+21x=10x+2 | | x+10/5=4 | | 1/7(14x-11)-3x=3/7 | | 11x-4=70 | | 84=x+(1-X)*69 | | 8x+2=7y | | 1+p/2=3 | | 1/24/1/3 | | 3/7x+6=3x | | 3/7x+6=3x | | ln(2x+3)=7 | | 4b/9-b/5=11 | | 4/3(3x-1)-2x=8/3 | | -9x+5x-5y= | | ln(8+x)=2 | | 5(x+10)=-75 | | 9(2d-7)= | | d/4-12=23 | | 3x^2+18x-94=3 | | X^4-4x^3+16x^2-24x+20=0 | | Z/4=-13-3z | | 12=3x-12 | | 4x^2-13x+12=4x+8 | | 4x-0=16 | | 4.2-1.49p+70=-9.7 | | (3u+7)(5-u)=0 | | 5/w=2 | | 5x(2+3)+14=70 | | -2(x+2)+5x=8 | | 4x+2-2x=3x-8 |